PENGARUH KUALITAS SUMBER DAYA MANUSIA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. CIPTA PRIMA KONTRINDO - Nopri Ariansyah; Mukran Roni (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to determine how much influence the quality of human resources and work motivation has on employee performance at PT. Cipta Prima Kontrindo. The method used in this research is a quantitative method. Data collection techniques in this study were observation and questionnaires with a total of 100 samples or people consisting of employees of PT. Cipta Prima Kontrindo. The results showed that the quality of human resources and work motivation simultaneously have a positive effect on employee performance. Evidenced by the results of the Fcount value of 11.902 greater than Ftable 3.09 with a significance of 0.000 less than 0.05 so that it can be stated to have a positive effect. Based on the test results of the coefficient of determination, R square is 0.197 or equal to 19.7%. This figure can be used to see the magnitude of the influence of the quality of human resources and work motivation on employee performance, while the remaining 80.3% is influenced by other variables outside the regression equation or variables not examined, for example discipline, environment and infrastructure.